Effectiveness of lake remediation towards water quality: application in Varsity Lake, University of Malaya, Kuala Lumpur - Nuzaima Che Mood,; Faridah Othman,; Noor Farahain Muhammad Amin,; Md. Ibrahim Adham, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Surface water quality monitoring is an important tool for enhancing the water body management system. This study focuses on the water quality of a lake based on rehabilitation work completed in 2014. This lake suffers from eutrophication and water quality degradation due to the increase in pollution rates and water source scarcity. Nine points were selected to represent the water quality status for the study area. Two river tributaries that pass through the University Malaya (UM) campus have been considered due of its potential as a water source for the lake. Field and laboratory analysis were conducted to understand the transport of water quality parameters. The data variations were analyzed using a multivariate statistical method to determine the significant differences between the lake and river. Based on the Malaysian Water Quality Index (WQI) and cluster analysis, the results indicated that the lake and river have different physico-chemical characteristics and the lake water has a better quality than the river. Comparison of the concentration for BOD, TSS, PO43- and NO3- between year 2009 and current study proved that the water quality has improved by 99.8% proving that the lake remediation is effective.